2019
DOI: 10.3992/1943-4618.14.4.93
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality Assessment for a Multistorey University Office Building in Malaysia

Abstract: The indoor air quality (IAQ) in office buildings should be assessed for public health concerns as it relates to work performance and productivity. Therefore, this paper aims to assess the IAQ in a university office building. From this investigation, the level of contaminated indoor air is examined, the significant causes and contributing factors of contaminated indoor air are determined and a recommendation to improve the existing condition has been proposed. The physical parameters measured include air temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This suggests that the majority (87%) of the participants concurred that inside ambiance attribute is an important factor that influences the efficiency of the activities of the users in the event centers. This corroborates the previous findings by Abdullah [11] that indoor ambiance attribute impacts on the workplace effecting and productivity of commercial buildings.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that the majority (87%) of the participants concurred that inside ambiance attribute is an important factor that influences the efficiency of the activities of the users in the event centers. This corroborates the previous findings by Abdullah [11] that indoor ambiance attribute impacts on the workplace effecting and productivity of commercial buildings.…”
Section: Resultssupporting
confidence: 92%
“…Yahaya, Hagos and Basrawi [1], research on indoor air quality in commercial buildings in Kautan unveiled that while some buildings have acceptable interior air quality, others have limited air movement, a lot of dust, and high temperatures. Abdullah [11], further the understanding on indoor air quality in Malaysian office buildings and analyzed public health issues about job performance and productivity. The study found that the building's indoor air quality was adequate and suitable for habitation despite the presence of countable symptoms of sick building syndrome (SBS) among its residents.…”
Section: Pollutants and Health Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a study stated that lethargy is the most prevalent SBS among office workers [27]. Another study stated that the respondents' most prevalent SBS symptom is dizziness [37]. Headache and tiredness are the dominant SBS symptoms [38].…”
Section: Sbs At the Officementioning
confidence: 99%
“…From a methodological perspective, a variety of scholarly work investigating the IEQ factors in relation to occupants' health, wellbeing and productivity are based on post occupation evaluation (POE) tools [19], such as BUS (Building Use Studies) Methodology [16,20], CBE (Centre for the Built Environmental) Berkeley Survey [21,22], Cost-Effective Open-Plan Environments (COPE) research [23], and BOSSA (Building Occupants Survey System Australia) [24]. Building on the IEQ related elements in these POE tools and findings from previous literature [8,11,25,26], this article focuses on the five IEQ aspects which affect the productivity of office workers, namely 1) thermal comfort [12,27,28], 2) indoor air quality [29,30], 3) lighting [31,32], 4) noise and acoustics [14,33,34], and 5) office layout [16,35].…”
Section: Literature Reviewmentioning
confidence: 99%